Waste Transformation Brings Blessings: P5RA Implementation and Technology Innovation in Sustainable Lifestyle: Transformasi Limbah Membawa Berkah: Penerapan P5RA dan Inovasi Teknologi dalam Gaya Hidup Berkelanjutan - Suciati, Suciati; Sucipto; Tobing, Victor Maruli Tua L (Indonesian Journal of Innovation Studies, 2025)
General Background: Environmental degradation caused by improper used cooking oil disposal is a growing concern in Indonesia. Specific Background: Although waste management has received scholarly attention, the integration of project-based environmental education within Islamic schools (madrasahs) remains underexplored. Knowledge Gap: Existing studies prioritize large-scale technical waste solutions, overlooking student involvement and curricular integration at the grassroots level. Aims: This study investigates the planning, implementation, and outcomes of the “P5RA – Transforming Waste into Blessings” initiative through project-based learning. Results: Conducted in Madrasah Tsanawiyah Negeri Bangkalan with 329 students, the program improved students’ character, creativity, and entrepreneurial skills by converting used cooking oil into marketable products like emergency stoves and aromatic candles. Novelty: This research introduces a unique integration of TPACK-based project learning, a DIY oil distillation device, digital literacy assessment tools, and an Islamic techno-ecopreneurship model—a first in madrasah contexts. Implications: Findings highlight the potential of structured, values-based project learning to foster environmental awareness, entrepreneurship, and character formation among students, offering a replicable model for other Islamic educational institutions seeking sustainable education practices.Highlight : Emphasizes project-based education through P5RA in managing used cooking oil waste. Integrates TPACK framework to foster environmental awareness and creativity. Strengthens students’ character and entrepreneurship through sustainable practices. Keywords : P5RA, TPACK, Used Cooking Oil, Waste Management, Sustainable Lifestyle